Numerical characterization of intraoperative and chronic electrodes in deep brain stimulation - Paffi, Alessandra; Camera, Francesca; Apollonio, Francesca; d’Inzeo, Guglielmo; Liberti, Micaela (Frontiers in Computational Neuroscience, 2015)
Intraoperative electrode is used in the Deep Brain stimulation (DBS) technique to pinpoint the brain target and to choose the best parameters for the stimulating signal. However, when the intraoperative electrode is replaced with the chronic one, the observed effects do not always coincide with predictions. To investigate the causes of such discrepancies, in this work, a 3D model of the basal ganglia has been considered and realistic models of both intraoperative and chronic electrodes have been developed and numerically solved. Results of simulations on the electric potential and the activating function along neuronal fibers show that the different geometries and sizes of the two electrodes do not change shapes and polarities of these functions, but only the amplitudes. A similar effect is caused by the presence of different tissue layers (edema or glial tissue) in the peri-electrode space. On the contrary, a not accurate positioning of the chronic electrode with respect to the intraoperative one (electric centers not coincident) may induce a complete different electric stimulation on some groups of fibers.